COVID‐19 and anatomy: Stimulus and initial response. Issue 3 (6th July 2020) - Brassett, Cecilia; Cosker, Thomas; Davies, D. Ceri; Dockery, Peter; Gillingwater, Thomas H.; Lee, T. Clive; Milz, Stefan; Parson, Simon H.; Quondamatteo, Fabio; Wilkinson, Tracey
Abstract : The outbreak of COVID‐19, resulting from widespread transmission of the SARS‐CoV‐2 virus, represents one of the foremost current challenges to societies across the globe, with few areas of life remaining untouched. Here, we detail the immediate impact that COVID‐19 has had on the teaching and practice of anatomy, providing specific examples of the varied responses from several UK, Irish and German universities and medical schools. Alongside significant issues for, and suspension of, body donation programmes, the widespread closure of university campuses has led to challenges in delivering anatomy education via online methods, a particular problem for a practical, experience‐based subject such as anatomy. We discuss the short‐term consequences of COVID‐19 for body donation programmes and anatomical education, and highlight issues and challenges that will need to be addressed in the medium to long term in order to restore anatomy education and practice throughout the world.